Green Accounting Policy for Water Transportation Services to Support Sustainable Tourism in the Lake Toba Area - Triana, Windi; Kemal, Lainatusshifa; Rahma, Annisa Alifa (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The Lake Toba area is not only an important tourism attraction in Indonesia, but also one of the five super priority tourist destinations that the Ministry of Tourism and Creative Economy focuses on, namely Lake Toba, Likupang, Borobudur, Mandalika, and Labuan Bajo. However, the rapid growth of tourism in the region has led to increased pressure on the environment and ecosystem of Lake Toba, including the negative impact of the water transportation sector which has the potential to damage the environment. The purpose of this study is to obtain the relationship between the green accounting policy of water transportation services and its driving factors including CSR programs for water transportation services, management support, and community support. The research methods used in this study are data collection on 65 samples of water transportation services, literature study, identifying problems, pre-processing, analyzing data, data analysis results, final evaluation, research approach with a mix method (qualitative and quantitative). Based on the results of the qualitative test of Nvivo data processing, the concept of green accounting policy carried out by water transportation business actors in Lake Toba tourist destinations is environmentally friendly technology, community support, management support and corporate social responsibility activities. This result is supported by the results of a quantitative test, namely the determination coefficient test where community support, management support and corporate social responsibility have an effect on green accounting policies.